Geology and Geochemistry of the Geyser Bight Geothermal Area, Umnak Island, Aleutian Islands, Alaska - Nye, C. J.; Motyka, R. J.; Turner, D. L.; Liss, S. A. (University of Alaska Fairbanks. Geophysical Institute., 1990)
The Geyser Bight geothermal area is located on Umnak Island in the central Aleutian Islands. It contains one of the hottest and most extensive areas of thermal springs and fumaroles in Alaska, and is only documented site in Alaska with geysers. The zone of hot springs and fumaroles lies at the head of Geyser Creek, 5 km up a broad, flat, alluvial valley from Geyser Bight. At present central Umnak is remote and undeveloped. This report describes results of a combined program of geologic mapping, K-Ar dating, detailed description of hot springs, petrology and geochemistry of volcanic and plutonic rock units, and chemistry of geothermal fluids. Our mapping documents the presence of plutonic rock much closer to the area of hotsprings and fumaroles than previously known, thus increasing the probability that plutonic rock may host the geothermal system. K-Ar dating of 23 samples provides a time framework for the eruptive history of volcanic rocks as well as a plutonic cooling age.